Positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and electric equipment

By using nickel-containing hydroxide as the precursor of the positive electrode material and controlling the multi-layer structure of the secondary particles, the problem of decreasing circulation stability of high nickel ternary layered materials is solved, and a balance between high capacity and high cycle stability is achieved.

CN119873910APending Publication Date: 2025-04-25GUANGXI CNGR NEW ENERGY SCI & TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411977423.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While improving capacity performance, the existing high-nickel ternary layered materials have significantly reduced circulation stability, making it difficult to find a balance between high capacity and high circulation stability.

Method used

Nickel-containing hydroxide is used as the precursor of the positive electrode material. The secondary particles have a multi-layer structure, the porosity of the intermediate layer is 40%-70%. By controlling the pH value and gas oxygen content in the co-precipitation reaction, a tree-like outer layer and inner layer are formed to improve the circulation stability of the material.

Benefits of technology

By forming a positive electrode material with a hollow structure, the capacity of the electrolyte and the embedded and deintercalation capabilities of lithium ions are increased, and the capacity performance of the lithium ion battery is improved. At the same time, due to the buffering effect of the loose structure, the circulation performance is improved and cracks during sintering are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873910A_ABST
    Figure CN119873910A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a positive electrode material precursor and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and electric equipment. The positive electrode material precursor contains secondary particles formed by primary particles; each secondary particle comprises an inner layer, a middle layer and an outer layer; the porosity of the middle layer is 40%-70%; the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.5): 1. The positive electrode material sintered by using the positive electrode material precursor provided by the invention has both capacity performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery, and electrical equipment. Background Art

[0002] As the application of lithium-ion batteries in the field of new energy vehicles gradually expands, cruising range has become a key factor restricting the development of new energy vehicles. Improving the energy density of lithium-ion batteries is an effective way to solve range anxiety.

[0003] High-nickel ternary layered materials are considered to be one of the most promising high-energy-density lithium-ion battery cathode materials due to their high specific capacity, low cost and relatively good safety. However, while high-nickel ternary layered materials improve capacity performance, their cycle stability shows a significant downward trend.

[0004] Therefore, there is an urgent need to develop a ternary cathode material precursor and cathode material that maintains high cycle stability under high capacity, so as to improve the comprehensive performance of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a positive electrode material precursor and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and electrical equipment, aiming to solve or at least alleviate the defects existing in the above-mentioned prior art.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positive electrode material precursor, wherein the positive electrode material precursor is a nickel-containing hydroxide; the positive electrode material precursor contains secondary particles composed of a plurality of primary particles; the secondary particles include an inner layer, an intermediate layer and an outer layer;

[0007] The porosity of the intermediate layer is 40%-70%; the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.5):1.

[0008] Optionally, the cathode material precursor satisfies at least one of the following conditions:

[0009] A. The porosity of the inner layer is 1%-20%; optionally, the porosity of the inner layer is 2%-18%;

[0010] B. The average radius of the inner layer is 0.4 μm-1.2 μm; optionally, the average radius of the inner layer is 0.6 μm-1.1 μm;

[0011] C. The porosity of the intermediate layer is 42%-65%;

[0012] D. The ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.4): 1;

[0013] E. The average thickness of the intermediate layer is 0.2 μm-0.7 μm; optionally, the average thickness of the intermediate layer is 0.3 μm-0.6 μm;

[0014] F. The porosity of the outer layer is 16%-50%; optionally, the porosity of the outer layer is 20%-40%;

[0015] G. The average thickness of the outer layer is 0.3 μm-1.0 μm; optionally, the average thickness of the outer layer is 0.4 μm-0.8 μm;

[0016] H. The total porosity of the secondary particles is 20%-55%; optionally, the total porosity of the secondary particles is 25%-40%.

[0017] I. The primary particles of the middle layer and the primary particles of the outer layer form a tree-like distribution.

[0018] Optionally, the primary particles on the surface of the secondary particles of the positive electrode material precursor meet at least one of the following conditions:

[0019] A. The average length of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 130nm-360nm; optionally, the average length of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 180nm-320nm;

[0020] B. The average width of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 3nm-25nm; optionally, the average width of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 5nm-16nm;

[0021] C. The average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is (10-31): 1; Optionally, the average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is (12-26): 1;

[0022] D. The primary particles on the surface of the secondary particles of the positive electrode material precursor are arranged in a staggered manner.

[0023] Optionally, the cathode material precursor satisfies at least one of the following conditions:

[0024] A. The sphericity of the secondary particles of the positive electrode material precursor is greater than 0.9;

[0025] B. The D50 of the precursor of the positive electrode material is 1.8 μm - 6.0 μm; optionally, the D50 of the precursor of the positive electrode material is 2.0 μm - 4.5 μm;

[0026] C. The BET specific surface area of the precursor of the positive electrode material is 45 m 2 / g - 65 m 2 / g;

[0027] D. The tap density TD of the precursor of the positive electrode material is 1.0 g / cm 3 -1.3 g / cm 3 ;

[0028] E. The particle size distribution Span = (D90 - D10) / D50 of the precursor of the positive electrode material is 0.6 - 1.1;

[0029] F. The precursor of the positive electrode material is nickel-containing hydroxide, and the molar amount of nickel in the nickel-containing hydroxide accounts for ≥ 60 mol% of the total metal;

[0030] G. The chemical formula of the precursor of the positive electrode material is Ni a Co b Mn c M d (OH) e X f ; wherein, 0.6 ≤ a < 1, 0 < b + c + d ≤ 0.4, 1.8 ≤ e ≤ 2.5, 0 ≤ f ≤ 0.2; M is selected from at least one of Mg, Nb, Zr, Y, Al, Zn, Ti, Sr, and X is B4O7 2- and / or MoO4 2- .

[0031] The second aspect of the present invention provides a method for preparing the precursor of the positive electrode material as described in the first aspect above. The method includes: under the protection of an inert gas, adding a nickel-containing metal salt solution, a precipitant solution, and a complexing agent solution into a reaction kettle containing a bottom liquid in a co-current manner for a coprecipitation reaction,

[0032] controlling the pH value in the coprecipitation reaction to have a pH value decline period T1, a pH value first plateau period T2, a pH value rise period T3, and a pH value second plateau period T4 in sequence.

[0033] Optionally, the method satisfies at least one of the following conditions:

[0034] (1) The pH value of the bottom liquid is 11.3 - 11.8;

[0035] (2) The ammonia concentration of the bottom liquid is 3 g / L - 7 g / L; optionally, the ammonia concentration of the bottom liquid is 3.5 g / L - 6.0 g / L;

[0036] (3) During the pH value decreasing period T1, the flow rate of the nickel-containing metal salt solution is controlled to be 6.0% / h-10.5% / h of the reactor volume;

[0037] (4) During the pH value decreasing period T1, the oxygen content of the gas in the reactor is controlled to be less than 2v%; alternatively, the oxygen content of the gas in the reactor is controlled to be less than 1v%;

[0038] (5) The reaction time of the pH value decrease period T1 is 2.5h-7.5h;

[0039] (6) During the pH value decreasing period T1, the stirring speed is controlled to be 800 rpm-1100 rpm;

[0040] (7) When the pH value reaches the first plateau period T2, the flow rate of the nickel-containing metal salt solution is controlled to be 5.0% / h-8.5% / h of the volume of the reactor;

[0041] (8) When the pH value reaches the first plateau period T2, the oxygen content of the gas in the reactor is controlled to be 2.0 v%-4.0 v%;

[0042] (9) The pH value of the first pH plateau period T2 is maintained at 11.0-11.4;

[0043] (10) When the pH value reaches the first plateau stage T2, the ammonia concentration in the reaction system is controlled to be 3 g / L-6 g / L;

[0044] (11) The reaction time of the first pH plateau phase T2 is 7.5h-14.5h;

[0045] (12) When the pH value reaches the first plateau phase T2, the stirring speed is controlled to be 800 rpm-1300 rpm;

[0046] (13) During the pH rising period T3 and the pH second plateau period T4, the flow rate of the nickel-containing metal salt solution is controlled to be 5.5% / h-8.5% / h of the reactor volume;

[0047] (14) During the pH rising period T3 and the pH second plateau period T4, the oxygen content of the gas in the reactor is controlled to be less than 1v%;

[0048] (15) The reaction time of the pH rising period T3 is 2h-5h;

[0049] (16) The pH value of the second pH plateau period T4 is maintained at 11.3-11.6;

[0050] (17) When the pH value reaches the second plateau stage T4, the ammonia concentration in the reaction system is controlled to be 3.0 g / L-5.5 g / L;

[0051] (18) The reaction time of the second pH plateau phase T4 is 25h-60h;

[0052] (19) During the pH rising period T3 and the pH second plateau period T4, the stirring speed is controlled to be 500 rpm-1050 rpm.

[0053] Optionally, the method satisfies at least one of the following conditions:

[0054] (1) The precipitant solution comprises a sodium hydroxide solution;

[0055] (2) The mass fraction of the precipitant solution is 20wt%-40wt%;

[0056] (3) the complexing agent solution includes an aqueous ammonia solution;

[0057] (4) The mass fraction of the complexing agent solution is 10wt%-30wt%;

[0058] (5) The nickel-containing metal salt solution also includes cobalt salt and / or manganese salt;

[0059] (6) The nickel-containing metal salt solution further contains a solution of a doping element M, wherein the doping element M is independently selected from at least one of Al, Ti, Zr, Cr, Mg, Ba, Nb or Sr;

[0060] (7) The sum of the molar concentrations of the metal ions in the nickel-containing metal salt solution is 1 mol / L to 3 mol / L;

[0061] (8) A solution containing an anion X is also introduced into the base liquid, wherein the anion X is MoO4 2- and / or WO4 2- ;

[0062] (9) A solution containing anions X is also introduced into the base liquid in parallel, wherein the mass concentration of the solution containing anions X is 2 g / L-10 g / L;

[0063] (10) The temperature of the coprecipitation reaction is controlled to be 50°C-70°C.

[0064] A third aspect of the present invention provides a positive electrode material for a lithium-ion battery, wherein the raw material of the positive electrode material for a lithium-ion battery includes the positive electrode material precursor described in the first aspect.

[0065] The fourth aspect of the present invention provides a lithium ion battery, comprising the lithium ion battery positive electrode material described in the third aspect; the lithium ion battery positive electrode material is a hollow structure.

[0066] A fifth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the fourth aspect.

[0067] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:

[0068] The secondary particles in the positive electrode material precursor provided by the present invention have a high porosity (40%-70%) in the middle layer and a large proportion of the middle layer (the ratio of the average thickness of the middle layer to the average radius of the secondary particles is (0.2-0.5):1). The positive electrode material sintered by the positive electrode material precursor provided by the present invention can form a hollow structure, accommodate more electrolyte, increase the contact area between the electrolyte and the lithium ion positive electrode material, and is beneficial to Li + The embedding and de-embedding of the intermediate layer can improve the capacity performance of the lithium-ion battery; at the same time, the loose structure of the intermediate layer can provide more buffer space for the gas escaping from the inner layer, thereby preventing cracking during sintering while taking into account the cycle performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1a is a surface SEM photograph of the positive electrode material precursor prepared in Example 2 of the present invention;

[0070] Figure 1b yes Figure 1a The surface SEM photos with the length and width of the primary particles marked after analysis by software;

[0071] Figure 2a is a cross-sectional SEM photograph of the positive electrode material precursor prepared in Example 2 of the present invention;

[0072] Figure 2b yes Figure 2a SEM photos of the delaminated cross-section after software analysis;

[0073] Figure 3a is a surface SEM photograph of the positive electrode material precursor prepared in Comparative Example 1 of the present invention;

[0074] Figure 3b yes Figure 3a The surface SEM photos with the length and width of the primary particles marked after analysis by software;

[0075] Figure 4a is a cross-sectional SEM photograph of the positive electrode material precursor prepared in Comparative Example 1 of the present invention;

[0076] Figure 4b yes Figure 4a SEM photos of the delaminated cross-section after software analysis;

[0077] Figure 5a is a surface SEM photograph of the positive electrode material precursor prepared in Comparative Example 2 of the present invention;

[0078] Figure 5b yes Figure 5a The surface SEM photos with the length and width of the primary particles marked after analysis by software;

[0079] Figure 6a is a cross-sectional SEM photograph of the positive electrode material precursor prepared in Comparative Example 2 of the present invention;

[0080] Figure 6b yes Figure 6a SEM photos of the delaminated cross-section after software analysis;

[0081] Figure 7 It is a schematic diagram of the calculation of the sphericity of secondary particles. DETAILED DESCRIPTION

[0082] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0083] As mentioned above, the first aspect of the present invention provides a positive electrode material precursor, wherein the positive electrode material precursor is a nickel-containing hydroxide; the positive electrode material precursor contains secondary particles composed of a plurality of primary particles; the secondary particles include an inner layer, an intermediate layer and an outer layer;

[0084] The porosity of the middle layer is 40%-70%; for example, it can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% or any value between 42%-45%, 45%-60%, 42%-65%; the average porosity of the middle layer is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% or any value between 42%-45%, 45%-60%, 42%-65%. The ratio of thickness to the average radius of the secondary particles is (0.2-0.5):1; for example, it can be 0.20:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1, 0.30:1, 0.32:1, 0.34:1, 0.36:1, 0.38:1, 0.40:1, 0.42:1, 0.44:1, 0.46:1, 0.48:1, 0.50:1 or any value between (0.2-0.3):1, (0.2-0.5):1, and (0.2-0.4):1.

[0085] Optionally, the porosity of the intermediate layer is 42%-65%; optionally, the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.4):1.

[0086] In the present invention, the porosity of the intermediate layer of the secondary particles in the positive electrode material precursor is controlled to be 40%-70%, and the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.5):1, so that the positive electrode material sintered by the positive electrode material precursor can form a hollow structure, accommodate more electrolyte, increase the contact area between the electrolyte and the lithium ion positive electrode material, and is beneficial to Li + The embedding and de-embedding of the intermediate layer can improve the capacity performance of the lithium-ion battery; at the same time, the loose structure of the intermediate layer can provide more buffer space for the gas escaping from the inner layer, thereby preventing cracking during sintering while taking into account the cycle performance of the lithium-ion battery; in addition, the loose structure of the intermediate layer can also reduce the sintering temperature.

[0087] In some embodiments, the porosity of the inner layer is 1%-20%, for example, it can be 1%, 3%, 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20% or any value between 1%-20%, 2%-18%, 1%-8%, 8%-18%, 18%-20%;

[0088] Optionally, the porosity of the inner layer is 2%-18%.

[0089] In the secondary particles in the positive electrode material precursor, the inner layer porosity is lower than that of the middle layer, and the structure is denser, which can maintain the structural stability of the secondary particles; while maintaining high capacity performance, it maintains a certain cycle stability.

[0090] In some embodiments, the average radius of the inner layer is 0.4 μm-1.2 μm, for example, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm or any value between 0.4 μm-1.2 μm, 0.4 μm-0.7 μm, 0.6 μm-1.1 μm, 0.7 μm-0.9 μm, 0.9 μm-1.2 μm;

[0091] Optionally, the average radius of the inner layer is 0.6 μm-1.1 μm.

[0092] In the secondary particles in the positive electrode material precursor, a suitable average radius of the inner layer combined with a suitable inner layer porosity can maintain the structural stability of the secondary particles; while improving high capacity performance, a certain cycle stability can be maintained.

[0093] In some embodiments, the average thickness of the intermediate layer is 0.2 μm-0.7 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or any value between 0.2 μm-0.7 μm, 0.2 μm-0.3 μm, 0.3 μm-0.5 μm, and 0.5 μm-0.7 μm;

[0094] Optionally, the average thickness of the intermediate layer is 0.3 μm-0.6 μm.

[0095] In the secondary particles of the cathode material precursor, the larger average radius of the middle layer combined with the higher porosity of the middle layer can form a hollow structure of the cathode material after sintering, which can accommodate more electrolyte and increase the contact area between the electrolyte and the cathode material, which is beneficial to Li + Embedding and de-embedding improve capacity performance; at the same time, during sintering, more buffer space is provided for the gas escaping from the inner layer to prevent cracking and avoid a significant decrease in cycle performance.

[0096] In some embodiments, the porosity of the outer layer is 16%-50%, for example, it can be 16%, 20%, 25%, 30%, 40%, 50% or any value between 16%-50%, 16%-23%, 16%-50%, 23%-41%, 41%-50%;

[0097] Optionally, the porosity of the outer layer is 20%-40%.

[0098] In the secondary particles in the positive electrode material precursor, the porosity of the outer layer is lower than that of the middle layer, and higher than that of the inner layer. The structure is loose, which is conducive to the penetration of electrolyte while maintaining a certain structural strength; while maintaining a certain cycle performance while improving capacity performance.

[0099] In some embodiments, the average thickness of the outer layer is 0.3 μm-1.0 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value between 0.3 μm-1.0 μm, 0.3 μm-0.5 μm, 0.5 μm-0.7 μm, 0.7 μm-1.0 μm;

[0100] Optionally, the outer layer has an average thickness of 0.4 μm-0.8 μm.

[0101] In the secondary particles in the positive electrode material precursor, a suitable average radius of the outer layer combined with a suitable outer layer porosity can maintain a certain cycle performance while improving the capacity performance.

[0102] In some embodiments, the total porosity of the secondary particles is 20%-55%, for example, it can be 20%, 25%, 30%, 40%, 50%, 55% or any value between 20%-55%, 20%-28%, 28%-40%, 40%-55%.

[0103] Optionally, the total porosity of the secondary particles is 25%-40%.

[0104] In the secondary particles in the positive electrode material precursor, by controlling the total porosity of the secondary particles, the number and volume of the total pores of the secondary particles can be controlled within a certain range, taking into account both capacity performance and cycle performance.

[0105] In some embodiments, the average length of the primary particles on the surface of the secondary particles of the cathode material precursor is 130nm-360nm, for example, it can be 130nm, 140nm, 150nm, 200nm, 250nm, 300nm, 360nm or any value between 130nm-360nm, 130nm-190nm, 190nm-250nm, 250nm-360nm, 180nm-320nm;

[0106] Optionally, the average length of primary particles on the surface of the secondary particles of the positive electrode material precursor is 180nm-320nm.

[0107] In some embodiments, the average width of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 3nm-25nm, for example, it can be 3nm, 4nm, 5nm, 10nm, 15nm, 20nm, 25nm or any value between 3nm-25nm, 3nm-9nm, 9nm-16nm, 16nm-25nm, and 5nm-16nm;

[0108] Optionally, the average width of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 5nm-16nm.

[0109] Among the secondary particles in the cathode material precursor, the primary particles on the surface are relatively slender, and the holes formed by the gaps are strip-shaped, which is conducive to sintering. + While ensuring the penetration of ions, it can also prevent segregation caused by excessive pore size, taking into account both capacity performance and cycle performance.

[0110] In some embodiments, the average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is (10-31): 1, for example, it can be 10: 1, 12: 1, 15: 1, 18: 1, 20: 1, 23: 1, 25: 1, 28: 1, 30: 1, 31: 1 or any value between (10-31): 1, (10-31): 1, (10-18): 1, (18-22): 1, (22-31): 1, (12-26): 1;

[0111] Optionally, the average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is (12-26): 1;

[0112] Among the secondary particles in the positive electrode material precursor, the average aspect ratio of the primary particles on the surface is within this range, and the stress generated by the volume deformation of the primary particles is small. This can suppress the microcracks caused by the volume change of the primary particles during contraction and expansion due to phase change during multiple cycles of the positive electrode material of the lithium-ion battery, while taking into account the cycle performance of the lithium-ion battery.

[0113] In some embodiments, primary particles on the surface of the secondary particles of the cathode material precursor are arranged in a staggered manner.

[0114] In some embodiments, the primary particles in the middle layer and the primary particles in the outer layer form a dendritic distribution;

[0115] Among the secondary particles in the positive electrode material precursor, the outer layer with a "tree-like" structure has good pressure bearing capacity and the intercrystalline stress generated by volume deformation is small. Therefore, it can suppress the microcracks caused by grain shrinkage and volume change during expansion caused by phase change during multiple cycles of the positive electrode material of the lithium-ion battery, while taking into account the cycle performance of the lithium-ion battery.

[0116] In some embodiments, the sphericity of the secondary particles of the cathode material precursor is greater than 0.9.

[0117] In some embodiments, the particle size D50 of the positive electrode material precursor is 1.8 μm-6.0 μm, for example, it can be 1.8 μm, 1.9 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm or any value between 1.8-6.0 μm, 2.0 μm-4.5 μm;

[0118] Optionally, the particle size D50 of the positive electrode material precursor is 2.0 μm-4.5 μm.

[0119] Compared with large-particle cathode material precursors, small-particle cathode material precursors have smaller secondary particle sizes and require lower sintering temperatures. During the sintering process, the lithium salt diffuses more fully within the precursor particles, and the resulting ternary cathode material has better electrochemical performance and a more stable particle structure. This structure is conducive to Li + The extraction and embedding of ions can improve the electrochemical properties of the materials.

[0120] In some embodiments, the specific surface area of ​​the cathode material precursor is 45 m 2 / g-65m 2 / g, for example, 45m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g or 45m 2 / g-65m 2 Any value between / g.

[0121] The secondary particles in the positive electrode material precursor have a higher specific surface area, which is beneficial to the penetration of lithium during sintering and the penetration of electrolyte after the battery is prepared, thereby improving the electrochemical properties of the material.

[0122] In some embodiments, the tap density TD of the cathode material precursor is 1.0 g / cm 3 -1.3g / cm 3 , for example, it can be 1.0 g / cm 3 , 1.05g / cm 3 , 1.10g / cm 3 , 1.15g / cm 3 , 1.20g / cm 3 , 1.25g / cm 3 , 1.30g / cm 3 or 1.0-1.3g / cm 3 Any value in between.

[0123] In some embodiments, the particle size distribution Span=(D90-D10) / D50 of the positive electrode material precursor is 0.6-1.1, for example, it can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 or any value between 0.6-1.1.

[0124] In some embodiments, the cathode material precursor is a nickel-containing hydroxide, wherein the molar amount of nickel in the nickel-containing hydroxide is ≥ 60 mol % of the total metal;

[0125] In some embodiments, the chemical formula of the positive electrode material precursor is Nia Co b Mn c M d (OH) e X f ; wherein, 0.6 ≤ a < 1, 0 < b + c + d ≤ 0.4, 1.8 ≤ e ≤ 2.5, 0 ≤ f ≤ 0.2; M is selected from at least one of Mg, Nb, Zr, Y, Al, Zn, Ti, Sr, and X is B4O7 2- and / or MoO4 2- ; optionally, M is selected from at least two of Mg, Nb, Zr, Y, Al, Zn, Ti, Sr;

[0126] Optionally, in the chemical formula of the cathode material precursor, a can be 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.96, 0.99 or any value between 0.6 ≤ a < 0.7, 0.7 ≤ a ≤ 0.8, 0.5 ≤ a ≤ 0.7, 0.70 ≤ a ≤ 0.99, b + c + d can be 0, 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40 or any value between 0 ≤ b + c + d ≤ 0.1, 0 ≤ b + c + d ≤ 0.2, 0 ≤ b + c + d ≤ 0.3, 0 ≤ b + c + d ≤ 0.4, 0.1 ≤ +c + d ≤ 0.3, 0.1 ≤ +c + d ≤ 0.4, e can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or any value between 1.8 ≤ e ≤ 2.5, and f can be 0, 0.02, 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20 or any value between 0 ≤ f ≤ 0.05, 0 ≤ t ≤ 0.1, 0.1 ≤ t ≤ 0.2.

[0127] In the secondary particles of the cathode material precursor, the multi - element doping can specifically improve a certain aspect of the battery performance to meet the customized needs of customers.

[0128] As described above, the second aspect of the present invention provides a method for preparing the cathode material precursor described in the first aspect above. The method includes: under the protection of an inert gas, adding a nickel - containing metal salt solution, a precipitant solution, and a complexing agent solution in a co - current manner into a reaction kettle containing a bottom liquid for co - precipitation reaction,

[0129] Controlling the pH value in the co - precipitation reaction to sequentially have a pH value decline period T1, a first pH value plateau period T2, a pH value rise period T3, and a second pH value plateau period T4.

[0130] It should be noted that, in the present invention, the first pH plateau T2 and the second pH plateau T4 in the coprecipitation reaction only indicate that the pH value maintains a stable reaction for a period of time as time goes by, and does not mean that the reaction parameters of the pH value of the first plateau T2 are the same or similar to those of the second plateau T2.

[0131] It should be noted that in the present invention, the pH value decrease period T1 corresponds to the period when the inner layer of the secondary particles in the positive electrode material precursor is formed; the pH value first plateau period T2 corresponds to the period when the middle layer of the secondary particles in the positive electrode material precursor is formed; the pH value increase period T3 and the pH value second plateau period T4 correspond to the period when the outer layer of the secondary particles in the positive electrode material precursor is formed.

[0132] In some embodiments, the inert gas includes N2.

[0133] In some embodiments, the pH value of the base solution is 11.3-11.8, for example, it can be 11.3, 11.4, 11.5, 11.6, 11.7, 11.8 or any value between 11.3 and 11.8.

[0134] It should be noted that the base liquid within the above pH range can ensure that the initial generation of the coprecipitation reaction meets the requirements.

[0135] In some embodiments, the ammonia concentration of the base solution is 3 g / L-7 g / L, for example, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L or any value between 3 g / L-7 g / L;

[0136] Optionally, the ammonia concentration of the base solution is 3.5 g / L-6.0 g / L.

[0137] It should be noted that the ammonia concentration in the present invention refers to the concentration of NH3·H2O, and the same applies hereinafter.

[0138] During the preparation process, the concentration of the complexing agent and the pH value in the base solution can affect the arrangement of primary particles in the inner layer of the subsequent initial reaction.

[0139] In some embodiments, during the pH decrease period T1, the flow rate of the nickel metal salt solution is controlled to be 6.0% / h-10.5% / h of the volume of the reactor, for example, it can be 6.0% / h, 6.5% / h, 7.0% / h, 7.5% / h, 8.0% / h, 8.5% / h, 9.0% / h, 9.5% / h, 10.0% / h, 10.5% / h or any value between 6.0% / h-10.5% / h.

[0140] In some embodiments, during the pH decrease period T1, the oxygen content of the gas in the reactor is controlled to be <2v%, for example, it can be any value within the range of <1.8v%, <1.5v%, <1.0v%, <0.8v%, <0.5v%, <0.4v%, <0.3v%, <0.2v%, <0.1v% or <2v%; optionally, the oxygen content of the gas in the reactor is controlled to be <1v%.

[0141] In some embodiments, the reaction time of the pH decrease period T1 is 2.5h-7.5h, for example, it can be 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or any value between 2.5h and 7.5h.

[0142] In some embodiments, during the pH value decrease period T1, the stirring speed is controlled to be 800 rpm-1100 rpm, for example, it can be 800 rpm, 900 rpm, 1000 rpm, 1100 rpm or any value between 800 rpm-1100 rpm;

[0143] In some embodiments, when the pH value reaches the first plateau period T2, the flow rate of the nickel-containing metal salt solution is controlled to be 5.0% / h-8.5% / h of the volume of the reactor, for example, 5.0% / h, 5.5% / h, 6.0% / h, 6.5% / h, 7.0% / h, 7.5% / h, 8.0% / h, 8.5% / h or any value between 5.0% / h-8.5% / h;

[0144] In some embodiments, during the first pH plateau period T2, the oxygen content of the gas in the reactor is controlled to be 2.0 v%-4.0 v%, for example, it may be 2.0 v%, 2.5 v%, 3.0 v%, 3.5 v%, 4.0 v% or any value between 2.0 v%-4.0 v%;

[0145] In some embodiments, the pH value of the first pH plateau period T2 is maintained at 11.0-11.4, for example, it can be 11.0, 11.1, 11.2, 11.3, 11.4 or any value between 11.0-11.4;

[0146] In some embodiments, during the first pH plateau period T2, the ammonia concentration in the reaction system is controlled to be 3 g / L-6 g / L, for example, 3 g / L, 4 g / L, 5 g / L, 6 g / L or any value between 3 g / L-6 g / L;

[0147] In some embodiments, the pH value of the first pH plateau period T2 is maintained at 10.8-11.2, for example, it can be 10.8, 10.9, 11.0, 11.1, 11.2 or any value between 10.8-11.2;

[0148] In some embodiments, the reaction time of the first pH plateau phase T2 is 7.5h-14.5h, for example, it can be 7.5h, 8h, 9h, 10h, 12h, 14h, 14.5h or any value between 7.5h-14.5h;

[0149] In some embodiments, when the pH value reaches the first plateau period T2, the stirring speed is controlled to be 800 rpm-1300 rpm, for example, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm or any value between 800 rpm and 1300 rpm;

[0150] In some embodiments, during the pH rising period T3 and the pH second plateau period T4, the flow rate of the nickel-containing metal salt solution is controlled to be 5.5% / h-8.5% / h of the reactor volume, for example, 5.5% / h, 6.0% / h, 6.5% / h, 7.0% / h, 7.5% / h, 8.0% / h, 8.5% / h or any value between 5.5% / h-8.5% / h;

[0151] In some embodiments, during the pH rising period T3 and the pH second plateau period T4, the oxygen content of the gas in the reactor is controlled to be <1v%, for example, it can be any value within the range of <1.0v%, <0.8v%, <0.5v%, <0.4v%, <0.3v%, <0.2v%, <0.1v% or <1v%;

[0152] In some embodiments, the reaction time of the pH rising period T3 is 2h-5h, for example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or any value between 2h-5h;

[0153] In some embodiments, the pH value of the second pH plateau period T4 is maintained at 11.3-11.6, for example, it can be 11.3, 11.4, 11.5, 11.6 or any value between 11.3-11.6;

[0154] In some embodiments, during the second pH plateau T4, the ammonia concentration in the reaction system is controlled to be 3.0 g / L-5.5 g / L, for example, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.5 g / L or any value between 3.0 g / L-5.5 g / L;

[0155] In some embodiments, the reaction time of the second pH plateau period T4 is 25h-60h, for example, it can be 25h, 30h, 40h, 50h, 60h or any value between 25h-60h;

[0156] In some embodiments, during the pH rising period T3 and the pH second plateau period T4, the stirring speed is controlled to be 500rpm-1050rpm, for example, it can be 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1050rpm or any value between 500rpm-1050rpm.

[0157] The v% of oxygen content in each stage mentioned above is the volume percentage of oxygen volume in the gas in the coprecipitation reactor to the total volume of gas in the reactor.

[0158] It should be noted that the primary particle size can be adjusted by controlling the oxygen content of the gas in the reactor at each stage of the coprecipitation reaction; when the oxygen content increases, the primary particles become smaller.

[0159] It should be noted that when other reaction parameters are the same, the particle size of the material increases with the increase of reaction time.

[0160] It should be noted that when the flow rate of the nickel metal salt solution is high, a large number of new primary particles tend to be generated; when the flow rate of the nickel metal salt solution is high, the size of the primary particles tends to increase; by adjusting the flow rate of the nickel metal salt solution at each stage of the co-precipitation reaction, the size of the primary particles in the corresponding area can be adjusted.

[0161] It should be noted that by controlling the change of pH value during the coprecipitation reaction, the primary particle generation rate, primary particle size and arrangement of primary particles can be adjusted, thereby affecting the porosity of different layers; specifically, the pH value during the coprecipitation reaction is first reduced (corresponding to the pH value decline period T1), and the time of pH decline is controlled. The coprecipitation reaction is more inclined to increase the size of the primary particles rather than generate new primary particles. After the size of the primary particles increases, the gaps between the primary particles will shrink, thereby making the inner layer dense, that is, the porosity of the inner layer is low; then when the pH value is stably maintained at a low level (corresponding to the first pH plateau period T 2) The number of newly generated primary particles is small, and other parameters are added, such as a high oxygen content that generates fine primary particles, thereby forming a loose middle layer, that is, the porosity of the middle layer is high; then the pH value during the co-precipitation reaction is increased (corresponding to the pH rising period T3), and the time of pH rising is controlled. The co-precipitation reaction is more inclined to generate new primary particles rather than increase the size of primary particles, thereby obtaining more primary particles. A large number of newly generated primary particles are aggregated outside the middle layer. Finally, a high pH value is maintained for a period of time (corresponding to the second pH plateau period T4), so that the middle layer and the outer layer form a tree-like structure.

[0162] It should be noted that stirring speed has an effect on porosity.

[0163] In some embodiments, the precipitant solution comprises sodium hydroxide solution.

[0164] In some embodiments, the mass fraction of the precipitant solution is 20wt%-40wt%, for example, it can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or any value between 20wt% and 40wt%.

[0165] In some embodiments, the complexing agent solution includes an aqueous ammonia solution.

[0166] In some embodiments, the mass fraction of the complexing agent solution is 10 wt%-30 wt%, for example, it can be 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt% or any value between 10 wt% and 30 wt%.

[0167] In some embodiments, the nickel-containing metal salt solution further comprises a cobalt salt and / or a manganese salt.

[0168] In some embodiments, the nickel-containing metal salt solution further contains a solution of a doping element M, and the doping element M is independently selected from at least one of Al, Ti, Zr, Cr, Mg, Ba, Nb or Sr.

[0169] In some embodiments, the sum of the molar concentrations of the metal ions in the nickel-containing metal salt solution is 1 mol / L-3 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L or any value between 1 mol / L-3 mol / L.

[0170] In some embodiments, a solution containing anions X is also introduced into the base solution, wherein the anions X are MoO4 2- and / or WO4 2- .

[0171] In some embodiments, a solution containing anions X is also flowed into the base liquid in parallel, and the mass concentration of the solution containing anions X is 2g / L-10g / L, for example, it can be 2g / L, 3g / L, 5g / L, 7g / L, 9g / L, 10g / L or any value between 2g / L-10g / L.

[0172] It should be noted that different doping elements and doping amounts of positive electrode material precursors, after being sintered into positive electrode materials and prepared into batteries, can enhance specific electrochemical properties and meet the differentiated needs of customers.

[0173] It should be noted that the pH value and ammonia concentration of the coprecipitation reaction can be adjusted by controlling the added precipitant solution and complexing agent solution.

[0174] In some embodiments, the temperature of the coprecipitation reaction is controlled to be 50°C-70°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C or any value between 50°C and 70°C.

[0175] It should be noted that the higher the temperature, the larger the primary particles formed.

[0176] It should be understood that the reaction of cathode material precursors is a multi-factor superposition, and analyzing the influence of a single factor when other conditions are different may lead to different conclusions.

[0177] The preparation method of the positive electrode material precursor of the present invention may also include post-processing means known in the art such as washing, drying, screening, demagnetization, and packaging, so as to obtain the positive electrode material precursor with better quality. The present invention will not be repeated here, and those skilled in the art should not understand it as a limitation of the present invention.

[0178] As mentioned above, the third aspect of the present invention provides a positive electrode material for a lithium-ion battery, wherein the raw material of the positive electrode material for a lithium-ion battery includes the positive electrode material precursor described in the first aspect.

[0179] The present invention has no particular restrictions on the method for preparing a positive electrode material for a lithium-ion battery using the positive electrode material precursor provided by the present invention, and those skilled in the art can select the method according to the technical means known in the art. However, in order to obtain a positive electrode material for a lithium-ion battery with better electrochemical performance, the present invention can optionally use the following method to prepare the positive electrode material for a lithium-ion battery.

[0180] According to an optional specific embodiment, the method for preparing the positive electrode material of a lithium ion battery comprises:

[0181] Evenly mixing the positive electrode material precursor and the lithium-containing compound to obtain a mixed material;

[0182] The mixed material is sintered under a sintering atmosphere to obtain the lithium ion battery positive electrode material.

[0183] In some embodiments, the lithium-containing compound is lithium hydroxide.

[0184] In some embodiments, the sintering conditions include: the sintering atmosphere is air, the initial temperature is 300°C-400°C; after keeping the temperature at the initial temperature for 1h-3h, the temperature is increased to 650°C-800°C, and then kept for 1h-3h.

[0185] In some embodiments, the amounts of the positive electrode material precursor and the lithium-containing compound are controlled so that the molar ratio of the Li element to the sum of the remaining metal elements in the mixture is 1.02-1.05:1.

[0186] It should be noted that the remaining metal elements in the present invention refer to the metal elements in the mixed material except the Li element.

[0187] As mentioned above, the fourth aspect of the present invention provides a lithium ion battery, comprising the lithium ion battery positive electrode material described in the third aspect; the lithium ion battery positive electrode material is a hollow structure. The hollow structure means that there is a hollow inner cavity (cavity) inside the secondary particle, or there are more cavities in the corresponding area, and the porosity is greater than 60%.

[0188] According to an optional specific implementation manner, the lithium ion battery is obtained by the following preparation method:

[0189] (1) Preparing a positive electrode sheet: the lithium ion battery positive electrode material, conductive acetylene black and binder are mixed in a mass ratio of 8:1:1 to obtain a slurry, and the slurry is evenly coated on the surface of an aluminum foil using a scraper and a coater, and then the coated aluminum foil is dried, and then pressed by a roller press for 5 times and cut into a circle with a diameter of 14 mm to 16 mm, and then transferred to a vacuum oven in a glove box for drying to obtain a positive electrode sheet;

[0190] (2) Battery assembly: The positive electrode sheet, negative electrode sheet (metallic lithium) and separator are wound into a battery core and then loaded into a battery steel shell. The core is then rolled, coated with sealing oil, welded with a battery cap and sealed with electrolyte. Finally, the battery is assembled after chemical sorting.

[0191] In some embodiments, the binder is a polytetrafluoroethylene solution with a mass fraction of 6 wt % to 10 wt %.

[0192] In some embodiments, the solvent in the polytetrafluoroethylene solution is N-methylpyrrolidone.

[0193] The present invention has no special requirements for the mixing conditions, and it is only necessary to mix the lithium-ion battery positive electrode material, the conductive acetylene black, and the binder uniformly. For example, the slurry mixer is operated at 2000 rpm-2400 rpm in the forward direction for 3 min-5 min, and reversed for 20 s-40 s as one cycle, and a total of 3-5 cycles are performed to achieve uniform mixing.

[0194] The present invention has no special requirements on the type of the diaphragm, and those skilled in the art can select one according to needs.

[0195] In some embodiments, the drying conditions include: a temperature of 60° C.-105° C. and a time of 2 h-4 h.

[0196] As mentioned above, the fifth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the fourth aspect.

[0197] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0198] Precipitant solution: sodium hydroxide solution, mass fraction is 32.5wt%.

[0199] Complexing agent solution: ammonia solution, mass fraction is 20wt%.

[0200] Example 1

[0201] Prepare a chemical formula Ni 0.92 Mn 0.08 The specific preparation method of the positive electrode material precursor of (OH)2 is as follows:

[0202] ①Raw material preparation:

[0203] Prepare a nickel-containing metal salt solution: mix battery-grade nickel sulfate, battery-grade manganese sulfate and pure water to obtain a nickel-containing metal salt solution, control the molar ratio of Ni:Mn in the nickel-containing metal salt solution to be 92:8, and the sum of the molar concentrations of nickel ions and manganese ions to be 2 mol / L;

[0204] ② Coprecipitation reaction

[0205] Preparation of base solution: In a reaction kettle, sodium hydroxide solution, ammonia solution and pure water are mixed to form a base solution, and the pH of the base solution is controlled to be 11.6, and the ammonia concentration in the base solution is 4.5 g / L;

[0206] pH value decrease period T1 (forming the inner layer of the secondary particles of the positive electrode material precursor): under the protection of N2, nickel-containing metal salt solution, sodium hydroxide solution and ammonia solution are added to the reactor containing the bottom liquid in parallel for co-precipitation reaction; first, the oxygen content of the gas in the reactor is controlled to be <0.5v%, the reaction temperature is 60°C, the stirring speed is 900rpm, the flow rate of the nickel-containing metal salt solution is 6.5% / h of the reactor volume, and the pH value of the pH value decrease period T1 decreases from 11.6 to 11.3, and the decrease time is 5h;

[0207] The first pH plateau period T2 (forming the middle layer of the secondary particles of the positive electrode material precursor): the oxygen content of the gas in the reactor during the coprecipitation reaction was then controlled to be 3.0v%, the stirring speed was 1000rpm, the flow rate of the nickel metal salt solution was 6.5% / h of the reactor volume, the pH value of the first pH plateau period T2 was maintained in the range of 11.25-11.35 and the reaction was continued for 8h, and the ammonia concentration was 4.3-4.7g / L;

[0208] pH rising period T3 and pH second plateau period T4 (forming the outer layer of the secondary particles of the cathode material precursor):

[0209] pH rising period T3: Then, during the coprecipitation reaction, the oxygen content of the gas in the reactor was controlled to be <0.5v%, the stirring speed was 900rpm, the flow rate of the nickel metal salt solution was 7.5% / h of the reactor volume, and the pH value of the pH rising period T3 rose to 11.5, and the rising time was 3h;

[0210] The second plateau period of pH value T4: Then, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be <0.5v%, and the pH value of the second plateau period of pH value T4 during the coprecipitation reaction was controlled to be maintained in the range of 11.45-11.55 and the reaction was continued for 35h, and the ammonia concentration was 4.5-4.9g / L;

[0211] Step 4 (post-processing): washing, drying, sieving, demagnetizing and packaging the stopped slurry in sequence to obtain the positive electrode material precursor.

[0212] Example 2

[0213] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0214] ② Coprecipitation reaction

[0215] Prepare the base solution: control the pH of the base solution to 11.7 and the ammonia concentration in the base solution to 5.5 g / L;

[0216] pH value decrease period T1: the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, and the pH value of the pH value decrease period T1 decreases from 11.7 to 11.3;

[0217] The first pH plateau period T2: the stirring speed is 1100 rpm, the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, the pH value of the first pH plateau period T2 is maintained in the range of 11.30-11.40 and the reaction is continued for 10 hours, and the ammonia concentration is 4.9-5.3 g / L;

[0218] pH rising period T3: the stirring speed is 850 rpm, the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, and the pH value of the pH rising period T3 rises to 11.4;

[0219] The second pH plateau period T4: The pH value of the second pH plateau period T4 was maintained in the range of 11.45-11.55 and the reaction continued for 36 hours, and the ammonia concentration was 5.2-5.6 g / L;

[0220] The unlisted parts are the same as those in Example 1, and are the same below.

[0221] Example 3

[0222] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0223] ② Coprecipitation reaction

[0224] Prepare the base solution: control the pH of the base solution to 11.5 and the ammonia concentration in the base solution to 4.0 g / L;

[0225] pH value decrease period T1: the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, and the pH value of the pH value decrease period T1 decreases from 11.5 to 11.2, and the decrease time is 6h;

[0226] The first pH plateau period T2: the stirring speed is 1100 rpm, the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, the pH value of the first pH plateau period T2 is maintained in the range of 11.15-11.25 and the reaction is continued for 12 hours, and the ammonia concentration is 3.7-4.1 g / L;

[0227] pH rising period T3: the stirring speed in the reactor is 850 rpm, the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, and the pH value in the pH rising period T3 rises to 11.4;

[0228] The second plateau period of pH value T4: The pH value of the second plateau period of pH value T4 during the coprecipitation reaction was then controlled to be maintained within the range of 11.45-11.55 and the reaction was continued for 32 hours, with an ammonia concentration of 3.9-4.3 g / L.

[0229] Example 4

[0230] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0231] ② Coprecipitation reaction

[0232] pH value decline period T1: the stirring speed is 950 rpm, the flow rate of the nickel metal salt solution is 7.5% / h of the reactor volume, and the pH value T1 in the decline period decreases from 11.6 to 11.3, and the decline time is 4 hours;

[0233] The first pH plateau period T2: the oxygen content of the gas in the reactor is 3.5v%, the stirring speed is 1200rpm, the flow rate of the nickel metal salt solution is 7.5% / h of the reactor volume, and the pH value of the first pH plateau period T2 is maintained in the range of 11.25-11.35 and the reaction is continued for 14h;

[0234] pH rising period T3: The reaction parameters of pH rising period T3 are the same as those in Example 1;

[0235] The second pH plateau period T4: The reaction time of the second pH plateau period T4 is 28 h.

[0236] Example 5

[0237] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0238] ② Coprecipitation reaction

[0239] Prepare the base solution: control the pH of the base solution to 11.5 and the ammonia concentration in the base solution to 4.0 g / L;

[0240] pH value decrease period T1: the oxygen content of the gas in the reactor is 1.5v%, the stirring speed is 1000rpm, the flow rate of the nickel metal salt solution is 10.0% / h of the reactor volume, and the pH value T1 of the pH value decrease period decreases from 11.5 to 11.2, and the decrease time is 3h;

[0241] The first pH plateau period T2: the stirring speed is 1100 rpm, the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, the pH value of the first pH plateau period T2 is maintained in the range of 11.15-11.25 and the reaction is continued for 10 hours, and the ammonia concentration is 3.7-4.1 g / L;

[0242] pH rising period T3: the stirring speed is 950 rpm, the flow rate of the nickel metal salt solution is 8.0% / h of the reactor volume, and the pH value of the pH rising period T3 rises to 11.4;

[0243] The second pH plateau period T4: The pH value of the second pH plateau period T4 was maintained in the range of 11.45-11.55 and the reaction continued for 30 hours, and the ammonia concentration was 3.9-4.3 g / L.

[0244] Example 6

[0245] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0246] ② Coprecipitation reaction

[0247] pH value decrease period T1: the stirring speed is 950 rpm, the flow rate of the nickel metal salt solution is 8.0% / h of the reactor volume, and the pH value T1 of the pH value decrease period decreases from 11.6 to 11.3, and the decrease time is 7h;

[0248] The first pH plateau period T2: the oxygen content of the gas in the reactor is 3.8v%, the stirring speed is 1200rpm, the flow rate of the nickel metal salt solution is 7.0% / h of the reactor volume, and the pH value of the first pH plateau period T2 is maintained in the range of 11.25-11.35 and the reaction is continued for 14h;

[0249] pH rising period T3: the stirring speed is 600 rpm, and the flow rate of the nickel metal salt solution is 6.0% / h of the reactor volume;

[0250] The second pH plateau phase T4: The second pH plateau phase T4 continued to react for 51 hours.

[0251] Example 7

[0252] Prepare a chemical formula Ni 0.75Co 0.10 Mn 0.12 Mg 0.03 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0253] ①Raw material preparation:

[0254] Prepare a nickel-containing metal salt solution: mix battery-grade nickel sulfate, battery-grade manganese sulfate, battery-grade magnesium sulfate and pure water to obtain a nickel-containing metal salt solution, control the molar ratio of Ni:Co:Mn:Mg in the nickel-containing metal salt solution to be 75:10:12:3, and the sum of the molar concentrations of nickel ions, cobalt ions, manganese ions and magnesium ions to be 2 mol / L;

[0255] ② Coprecipitation reaction

[0256] pH value decrease period T1: the stirring speed is 950 rpm, the flow rate of the nickel metal salt solution is 8.5% / h of the reactor volume, and the pH value decrease period decreases for 4 hours;

[0257] The first pH plateau period T2: the oxygen content of the gas in the reactor is 2.5v%, the rotation speed is 900rpm, the flow rate of the nickel metal salt solution is 5.5% / h of the reactor volume, and the reaction time of the first pH plateau period T2 is 10h;

[0258] pH rising period T3: The reaction parameters of pH rising period T3 are the same as those in Example 1;

[0259] The second pH plateau phase T4: The reaction time of the second pH plateau phase T4 is 36 h.

[0260] Example 8

[0261] Prepare a chemical formula Ni 0.8 Co 0.1 Mn 0.1 (OH) 1.96 (MoO4) 0.02 The positive electrode material precursor has the following reaction conditions different from those in Example 1:

[0262] ①Raw material preparation:

[0263] Prepare a nickel-containing metal salt solution: mix battery-grade nickel sulfate, battery-grade cobalt sulfate, battery-grade manganese sulfate and pure water to obtain a nickel-containing metal salt solution, control the molar ratio of Ni:Co:Mn in the nickel-containing metal salt solution to be 80:10:10, and the sum of the molar concentrations of nickel ions, cobalt ions and manganese ions to be 2 mol / L;

[0264] Prepare a solution doped with element M: weigh battery-grade sodium molybdate to prepare a sodium molybdate solution having a molybdenum content of 7.99 g / L;

[0265] The nickel-containing metal salt solution and the sodium molybdate solution are fed simultaneously, and the flow rate ratio of the nickel-containing metal salt solution to the sodium molybdate solution is 1:0.5;

[0266] ② Coprecipitation reaction

[0267] Prepare the base solution: control the pH of the base solution to 11.4 and the ammonia concentration in the base solution to 3.5 g / L;

[0268] pH value decreasing period T1: the stirring speed is 1000 rpm, the flow rate of the nickel metal salt solution is 8.5% / h of the reactor volume, and the pH value T1 of the pH value decreasing period decreases from 11.4 to 11.1;

[0269] The first pH plateau period T2: the oxygen content of the gas in the reactor is 3.5v%, the rotation speed is 1100rpm, the flow rate of the nickel metal salt solution is 8.0% / h of the reactor volume, the pH value of the first pH plateau period T2 is maintained in the range of 11.05-11.15 and the reaction is continued for 10h, and the ammonia concentration is 3.3-3.7g / L;

[0270] pH rising period T3: the stirring speed is 950 rpm, the flow rate of the nickel metal salt solution is 8.0% / h of the reactor volume, pH second plateau period T4: the pH value of the pH second plateau period T4 is maintained in the range of 11.25-11.35 and the reaction continues for 37 hours.

[0271] Comparative Example 1

[0272] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0273] ② Coprecipitation reaction

[0274] Prepare the base solution: control the pH of the base solution to 12.3 and the ammonia concentration in the base solution to 9.0 g / L;

[0275] The first step (forming the inner layer of the secondary particles of the positive electrode material precursor): first, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be 3.5v%, the reaction temperature was 55°C, the stirring speed was 1200rpm, the flow rate of the nickel metal salt solution was 12.0% / h of the reactor volume, and the pH value of the pH drop period T1 dropped from 12.3 to 11.45-11.55, and the drop time was 4h;

[0276] Step 2 (forming the outer layer of the secondary particles of the positive electrode material precursor): Then, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be <1.0v%, the stirring speed was 600rpm, the flow rate of the nickel metal salt solution was 2.0% / h of the reactor volume, the pH value of the first plateau period T2 was maintained in the range of 11.45-11.55, and the reaction was continued for 40h, and the ammonia concentration was 8.4-8.8g / L;

[0277] Step 3: Stop the reaction, wash, dry, sieve, demagnetize and package the slurry in the reactor in sequence to obtain the positive electrode material precursor.

[0278] Comparative Example 2

[0279] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0280] ② Coprecipitation reaction

[0281] Prepare the base solution: control the pH of the base solution to 12.0 and the ammonia concentration in the base solution to 8.0 g / L;

[0282] pH value decreasing period T1: First, the stirring speed during the coprecipitation reaction was controlled to be 1100 rpm, the flow rate of the nickel metal salt solution was 11.0% / h of the reactor volume, and the pH value during the pH value decreasing period T1 decreased from 12.0 to 11.4;

[0283] pH value first plateau period T2: Then, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be 1.5v%, the stirring speed was 700rpm, the flow rate of the nickel metal salt solution was 3.0% / h of the reactor volume, the pH value of the pH value first plateau period T2 was maintained in the range of 11.35-11.45 and the reaction was continued for 3h, and the ammonia concentration was 7.4-7.8g / L;

[0284] pH rising period T3: Then, the stirring speed during the coprecipitation reaction was controlled to be 500 rpm, the flow rate of the nickel metal salt solution was 5.0% / h of the reactor volume, and the pH value of the pH rising period T3 rose to 11.7, and the rising time was 8 hours;

[0285] The second plateau period of pH value T4: The pH value of the second plateau period of pH value T4 during the coprecipitation reaction was then controlled to be maintained within the range of 11.65-11.75 and the reaction was continued for 44 hours, with an ammonia concentration of 7.6-8.0 g / L.

[0286] Comparative Example 3

[0287] Prepare a chemical formula Ni 0.92 Mn 0.08The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0288] ② Coprecipitation reaction

[0289] Prepare the base solution: control the pH of the base solution to 11.8 and the ammonia concentration in the base solution to 8.0 g / L;

[0290] pH value decreasing period T1: First, the stirring speed during the coprecipitation reaction was controlled to be 950 rpm, the flow rate of the nickel metal salt solution was 8.5% / h of the reactor volume, and the pH value during the pH value decreasing period T1 decreased from 11.8 to 11.4;

[0291] pH value first plateau period T2: Then, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be 1.5v%, the stirring speed was 700rpm, the flow rate of the nickel metal salt solution was 3.0% / h of the reactor volume, the pH value of the pH value first plateau period T2 was maintained in the range of 11.35-11.45 and the reaction was continued for 10h, and the ammonia concentration was 6.6-7.0g / L;

[0292] pH rising period T3: Then, the stirring speed during the coprecipitation reaction was controlled to be 600 rpm, the flow rate of the nickel metal salt solution was 6.0% / h of the reactor volume, and the pH value of the pH rising period T3 rose to 11.6, and the rising time was 3 hours;

[0293] The second plateau period of pH value T4: Then, during the coprecipitation reaction, the pH value of the second plateau period of pH value T4 was controlled to be maintained in the range of 11.55-11.65 and the reaction was continued for 33 hours, and the ammonia concentration was 7.4-7.8 g / L.

[0294] Comparative Example 4

[0295] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0296] ② Coprecipitation reaction

[0297] Prepare the base solution: control the pH of the base solution to 11.6 and the ammonia concentration in the base solution to 5.0 g / L;

[0298] pH value decrease period T1: First, the stirring speed during the coprecipitation reaction was controlled to be 950 rpm, the flow rate of the nickel metal salt solution was 8.0% / h of the reactor volume, and the pH value during the pH value decrease period T1 decreased from 12.0 to 11.4, and the decrease time was 4 hours;

[0299] pH value first plateau period T2: Then, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be 3.5v%, the stirring speed was 900rpm, the flow rate of the nickel metal salt solution was 5.5% / h of the reactor volume, the pH value of the pH value first plateau period T2 was maintained in the range of 11.35-11.45 and the reaction was continued for 3h, and the ammonia concentration was 4.4-4.8g / L;

[0300] pH value rising period T3: Then, the stirring speed in the reactor is controlled to be 800 rpm during the coprecipitation reaction, the flow rate of the nickel metal salt solution is 6.5% / h of the reactor volume, and the reaction time of the pH value rising period T3 is 8h;

[0301] The second plateau phase T4 of pH value: Then, the second plateau phase T4 of pH value during the coprecipitation reaction was controlled to continue the reaction for 75 hours.

[0302] Comparative Example 5

[0303] Prepare a chemical formula Ni 0.92 Mn 0.08 The positive electrode material precursor of (OH)2, the reaction conditions different from those in Example 1 are:

[0304] ② Coprecipitation reaction

[0305] Prepare the base solution: control the pH of the base solution to 11.2 and the ammonia concentration in the base solution to 2.5 g / L;

[0306] pH value decrease period T1: First, the stirring speed during the coprecipitation reaction was controlled to be 950 rpm, the flow rate of the nickel metal salt solution was 6.0% / h of the reactor volume, and the pH value during the pH value decrease period T1 decreased from 12.0 to 10.7, and the decrease time was 3 hours;

[0307] pH value first plateau period T2: Then, the oxygen content of the gas in the reactor during the coprecipitation reaction was controlled to be 5.5v%, the stirring speed was 800rpm, the flow rate of the nickel metal salt solution was 5.0% / h of the reactor volume, the pH value of the pH value first plateau period T2 was maintained in the range of 10.65-10.75 and the reaction was continued for 20h, and the ammonia concentration was 2.0-2.4g / L;

[0308] pH rising period T3: Then, the flow rate of the nickel metal salt solution during the coprecipitation reaction was controlled to be 7.0% / h of the reactor volume, and the pH value of the pH rising period T3 rose to 11.2, and the rising time was 1h;

[0309] The second pH plateau period T4: The flow rate of the nickel metal salt solution during the coprecipitation reaction was then controlled to be 7.0% / h of the reactor volume, and the pH value of the second pH plateau period T4 was maintained within the range of 11.15-11.25 to continue the reaction for 15 hours, with an ammonia concentration of 2.3-2.7 g / L.

[0310] Test Example 1

[0311] The positive electrode material precursor prepared in the above example was tested for physical and chemical data, specifically:

[0312] 1. The particle size D50, D10 and D90 of the secondary particles are measured by a laser particle size tester (instrument model: Mastersizer3000) in accordance with the national standard GB / T 19077-2016 Particle Size Analysis Laser Diffraction Method;

[0313] 2. Specific surface area (BET method): measured by fully automatic nitrogen adsorption specific surface area analyzer (instrument model: BELPREP-VACII / BELSORP-MINI-X), referring to the national standard "GB / T 19587-2017 Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method";

[0314] 3. Tap density (TD): measured by powder tap density tester (model: Dandong Better BT-302), referring to the national standard "GB / T 5162-2021 Determination of tap density of metal powder";

[0315] 4. Contents of nickel, cobalt, manganese, etc.: Determined by inductively coupled plasma mass spectrometry (instrument model: Agilent7850ICP-MS), referring to the national standard "GB / T 8647.11-2019 Nickel Chemical Analysis Method Part 11_Determination of Magnesium, Aluminum, Manganese, Cobalt, Copper, Zinc, Cadmium, Tin, Antimony, Lead and Bismuth Content Inductively Coupled Plasma Mass Spectrometry".

[0316] 5. Microstructure test of secondary particles of cathode material precursor involved in this application:

[0317] ① The calculation method of the sphericity of secondary particles is: adjust the scanning electron microscope (SEM) to an appropriate magnification and take a photo to obtain the surface SEM photo of the secondary particles of the cathode material precursor, and then use Image-ProPlus software to analyze the surface SEM photo and calculate the sphericity directly; it can also be assumed that the orthographic projection shape of the secondary particles is a circle, and the sphericity is πr 面积 2 and πr 周长 2 The ratio is calculated, that is, sphericity = 4πS / C 2, where S is the area of ​​the precursor particle in the electron microscope (the area is calculated as the total area of ​​the pixels, which is also the equivalent area circle), and C is the perimeter of the precursor particle in the electron microscope (the perimeter is obtained as the total length of the edges of the secondary particle pixels). For example, Figure 7 As shown, the black area is the projected area S of the secondary particles, and the green curve is the projected perimeter C, r 面积 is the radius of a circle with the same area as the secondary particle (half the diameter of the circle with equivalent area), r 周长 is the radius of a circle with the same circumference as the secondary particle (half the diameter of the equivalent circumference circle), then r 面积 2 =S / π, r 周长 =C / 2π,

[0318]

[0319] ② Specific test method for each porosity of secondary particles: Adjust the scanning electron microscope (SEM) to a suitable magnification and take pictures to obtain the cross-sectional SEM photos of the secondary particles of the positive electrode material precursor, and then analyze the cross-sectional SEM photos by Image-Pro Plus software and calculate the various porosities. The calculation formula is: total porosity = [(the sum of the areas of the pores of the secondary particles in the cross section / the cross-sectional area of ​​the secondary particles) × 100] (%); inner layer porosity = [(the sum of the areas of the pores of the inner layer of the secondary particles in the cross section / the cross-sectional area of ​​the inner layer of the secondary particles) × 100] (%); middle layer porosity = [(the sum of the areas of the pores of the middle layer of the secondary particles in the cross section / the cross-sectional area of ​​the middle layer of the secondary particles) × 100] (%); outer layer porosity = [(the sum of the areas of the pores of the outer layer of the secondary particles in the cross section / the cross-sectional area of ​​the outer layer of the secondary particles) × 100] (%). For example, the magnification of the cross-sectional SEM photograph may be 7.0K, 9.0K, 10.0K, etc. The specific magnification is preferably such that there is only one complete or nearly complete cross-sectional image of a single secondary particle sphere in the SEM field of view.

[0320] The cross-section stratification standard of the secondary particles is: stratification is performed according to the different morphologies of the primary particles in different regions and the different pore sizes formed. For example, the radius of the inner layer, the thickness of the middle layer and the thickness of the outer layer after stratification are as follows: Figure 2bAs shown, the inner layer is fitted into a circle 1 according to the equal area method, and the radius of circle 1 is the radius of the inner layer; the inner layer and the middle layer are fitted into a circle 2 according to the equal area method, and the radius of circle 2 is the thickness of the middle layer + the radius of the inner layer; the entire cross section is fitted into a circle 3 according to the equal area method, and the radius of circle 3 is the thickness of the outer layer + the thickness of the middle layer + the radius of the inner layer; and then the thickness of the middle layer and the thickness of the outer layer are calculated. The average radius of the secondary particles, the average radius of the inner layer, the average thickness of the middle layer, and the average thickness of the outer layer are the average values ​​of the measured data of the cross-section SEM images of the secondary particles of the positive electrode material precursor within the range of D50±0.5μm. For example, the multiple can be 3, 5, 10, etc.

[0321] ③ The test method for primary particles on the surface of secondary particles is: select the SEM photo of the secondary particle surface of the positive electrode material precursor with the largest magnification, and take the longest straight-line distance between the two ends of the selected surface primary particle in the surface SEM photo as the length, and take the longest straight-line distance between the two ends perpendicular to the length line as the width, measure the length and width of multiple surface primary particles, and then calculate the aspect ratio of multiple surface primary particles respectively; finally, calculate the average length, average width, and average aspect ratio (average value of the aspect ratio) of multiple surface primary particles respectively. In the above measurement, if there is a situation where a primary particle is blocked, the unblocked part is assumed to be a complete primary particle for measurement. Exemplarily, the magnification of the surface SEM photo can be 50.0K, etc.

[0322] For example, the microstructure of the cathode material precursors prepared in the above-mentioned Example 2 and Comparative Example 1-Comparative Example 2 was tested, as shown in FIG. Figure 1a-Figure 6b As shown:

[0323] pass Figure 1a and Figure 1b It can be seen that the primary particles on the surface of the secondary particles of the cathode material precursor provided by the present invention are arranged in a staggered manner; Figure 1a The picture shows the original SEM photo of the surface; Figure 1b The figure shows the surface SEM photo after image analysis by Image-ProPlus software, which has marked the outlines of multiple primary particles (see blue outlines) and the length and width of some primary particles (see white marks and numbers), the same below;

[0324] pass Figure 2a and Figure 2b It can be seen that the secondary particles in the positive electrode material precursor provided by the present invention include an inner layer, an intermediate layer and an outer layer, and the primary particles in the intermediate layer and the primary particles in the outer layer form a tree-like distribution; the primary particles on the surface of the positive electrode material precursor are arranged in a staggered manner; wherein, Figure 2a This is the original SEM photo of the cross section; Figure 2bThis is a processed image of the cross-section SEM photo that has been layered and the pore area marked after image analysis by Image-Pro Plus software. Specifically, the inner layer is the red circle and the circular area within the red circle, the red area inside the circular area is the pore area of ​​the inner layer, the middle layer is the inner ring area between the green circle and the red circle, the green area within the inner ring area is the pore area of ​​the middle layer, the outer layer is the outer ring area between the blue-green circle and the green circle, and the blue area within the outer ring area is the pore area of ​​the outer layer; the rules for layering and marking the pore area of ​​each layer are the same below.

[0325] pass Figure 3a and Figure 3b It can be seen that the primary particles on the surface of the secondary particles of the positive electrode material precursor prepared in Comparative Example 1 are in the shape of laths, and the primary particles are relatively coarse;

[0326] pass Figure 4a and Figure 4b It can be seen that the secondary particles in the positive electrode material precursor prepared in Comparative Example 1 have a two-layer structure, with a loose inner layer and a dense outer layer;

[0327] pass Figure 5a and Figure 5b It can be seen that the primary particles on the surface of the secondary particles of the positive electrode material precursor prepared in Comparative Example 2 are in the shape of laths, and the primary particles are relatively coarse;

[0328] pass Figure 6a and Figure 6b It can be seen that the cathode material precursor prepared in Comparative Example 2 has a three-layer structure, the inner layer and the outer layer are thicker and denser, and the middle layer is thinner and looser;

[0329] The above test results are shown in Tables 1 to 3.

[0330] Table 1 Parameters of cathode material precursor 1

[0331]

[0332]

[0333] Table 2 Parameters of cathode material precursor 2

[0334]

[0335] Table 3 Parameters of cathode material precursor 3

[0336]

[0337]

[0338] Test Example 2

[0339] Preparation of positive electrode materials for lithium-ion batteries:

[0340] The positive electrode material precursors prepared in the aforementioned embodiments and comparative examples and lithium hydroxide are uniformly mixed to obtain a mixed material;

[0341] The molar ratio of the Li element to the sum of the remaining metal elements (metal elements other than the Li element) in the mixture is controlled to be 1.05:1;

[0342] Sintering the mixed material in an air atmosphere to obtain the positive electrode material for a lithium-ion battery;

[0343] Sintering conditions: initial temperature of 350°C for 2 h, then heating to 700°C and keeping for another 2 h.

[0344] Test Example 3

[0345] Preparation of lithium-ion battery (button battery model is CR-2032 half-cell):

[0346] (1) Preparation of positive electrode sheet: The lithium ion battery positive electrode material obtained in Test Example 2 was mixed with conductive acetylene black and a binder (polytetrafluoroethylene solution with a mass fraction of 8 wt%, and the solvent was N-methylpyrrolidone) in a mass ratio of 8:1:1 (running in a slurry mixer at 2200 rpm for 4 min and reverse rotation for 30 s as one cycle, and a total of 3 cycles were performed to achieve uniform mixing) to obtain a slurry, and the slurry was evenly coated on the surface of an aluminum foil using a 200 μm scraper and a coater, and then the coated aluminum foil was dried (temperature 80° C., time 3 h), and then pressed 3 times by a roller press, cut into a circle with a diameter of 15 mm, and then transferred to a vacuum oven in a glove box for drying to obtain a positive electrode sheet;

[0347] (2) Battery assembly: The positive electrode sheet, negative electrode sheet (metallic lithium) and separator are wound into a battery core and then loaded into a battery steel shell. The core is then rolled, coated with sealing oil, welded with a battery cap and sealed with electrolyte. Finally, the battery is assembled after chemical sorting.

[0348] The assembled battery was discharged for the first time (3.0-4.5V) at room temperature (25°C), and the first discharge capacity at 0.1C and 1C, and the capacity retention rate after 50 cycles at 1C current were tested. 1C = 210 mAh / g. The results are shown in Table 4.

[0349] Table 4

[0350]

[0351]

[0352] It can be seen from the above results that the porosity of the intermediate layer of the secondary particles in the positive electrode material precursors of Examples 1-8 of the present invention is high (40%-70%) and the intermediate layer accounts for a large proportion (the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.5): 1). The positive electrode material sintered from the positive electrode material precursor provided by the present invention can take into account both capacity performance and cycle performance.

[0353] Compared with Example 1, the battery prepared from the positive electrode material precursor product of Comparative Example 1 shows lower 0.1C first discharge capacity and 1C / 0.1C rate performance, and it is speculated that the possible reason is that there is no loose intermediate layer; the battery prepared from the positive electrode material precursor product of Comparative Example 2 shows lower 0.1C first discharge capacity and 1C / 0.1C rate performance, and it is speculated that the possible reason is that the intermediate layer thickness ratio and porosity are too small; the battery prepared from the positive electrode material precursor product of Comparative Example 3 shows lower 0.1C first discharge capacity and 1C / 0.1C rate performance, and it is speculated that the possible reason is that the intermediate layer porosity is too low; the battery prepared from the positive electrode material precursor product of Comparative Example 4 shows lower 0.1C first discharge capacity and 1C / 0.1C rate performance, and it is speculated that the possible reason is that the intermediate layer thickness ratio is too low; the battery prepared from the positive electrode material precursor of Comparative Example 5 shows poor 1C cycle 50 capacity retention rate, and it is speculated that the intermediate layer thickness ratio is too high.

[0354] Among them, Examples 1-4 are 9-series nickel manganese hydroxides, and the prepared batteries show higher capacity performance and rate performance. Compared with Example 3, the positive electrode material precursor prepared in Example 5 shows slightly better 0.1C first discharge capacity and 1C / 0.1C rate performance after being prepared into a battery, and the capacity retention rate of 1C cycles 50 times is slightly worse. It is speculated that the possible reasons are that the inner layer radius is too small and the inner layer porosity is too high. Compared with Example 2, the positive electrode material precursor prepared in Example 6 shows slightly worse 0.1C first discharge capacity and 1C / 0.1C rate performance after being prepared into a battery, and the capacity retention rate of 1C cycles 50 times is slightly better. It is speculated that the possible reasons are that the outer layer thickness accounts for too high a proportion and the outer layer porosity is too low. Example 7 is a 7-series nickel-cobalt-manganese hydroxide doped with magnesium, and Example 8 is an 8-series nickel-cobalt-manganese hydroxide doped with molybdate. The prepared batteries have good electrochemical performance. It is speculated that the possible reasons are that the porosity of the intermediate layer is high (40%-70%) and the intermediate layer accounts for a large proportion (the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.5): 1). It is also applicable to 7-series, 8-series and various doping situations.

[0355] The optional implementation modes of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cathode material precursor, characterized in that: The positive electrode material precursor is a nickel-containing hydroxide; the positive electrode material precursor contains secondary particles composed of a plurality of primary particles; the secondary particles include an inner layer, an intermediate layer and an outer layer; The porosity of the intermediate layer is 40%-70%; the ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.5):

1.

2. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: A. The porosity of the inner layer is 1%-20%; optionally, the porosity of the inner layer is 2%-18%; B. The average radius of the inner layer is 0.4 μm-1.2 μm; optionally, the average radius of the inner layer is 0.6 μm-1.1 μm; C. The porosity of the intermediate layer is 42%-65%; D. The ratio of the average thickness of the intermediate layer to the average radius of the secondary particles is (0.2-0.4): 1; E. The average thickness of the intermediate layer is 0.2 μm-0.7 μm; optionally, the average thickness of the intermediate layer is 0.3 μm-0.6 μm; F. The porosity of the outer layer is 16%-50%; optionally, the porosity of the outer layer is 20%-40%; G. The average thickness of the outer layer is 0.3 μm-1.0 μm; optionally, the average thickness of the outer layer is 0.4 μm-0.8 μm; H. The total porosity of the secondary particles is 20%-55%; optionally, the total porosity of the secondary particles is 25%-40%. I. The primary particles of the middle layer and the primary particles of the outer layer form a tree-like distribution.

3. The cathode material precursor according to claim 1 or 2, characterized in that: The primary particles on the surface of the secondary particles of the positive electrode material precursor meet at least one of the following conditions: A. The average length of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 130nm-360nm; optionally, the average length of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 180nm-320nm; B. The average width of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 3nm-25nm; optionally, the average width of the primary particles on the surface of the secondary particles of the positive electrode material precursor is 5nm-16nm; C. The average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is (10-31): 1; Optionally, the average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is (12-26): 1; D. The primary particles on the surface of the secondary particles of the positive electrode material precursor are arranged in a staggered manner.

4. The cathode material precursor according to any one of claims 1 to 3, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: A. The sphericity of the secondary particles of the positive electrode material precursor is greater than 0.9; B. The particle size D50 of the positive electrode material precursor is 1.8 μm-6.0 μm; C. The specific surface area of ​​the positive electrode material precursor is 45 m 2 / g-65m 2 / g; D. The tap density TD of the positive electrode material precursor is 1.0 g / cm 3 -1.3g / cm 3 ; E. The particle size distribution Span of the positive electrode material precursor is (D90-D10) / D50 is 0.6-1.1; F. The positive electrode material precursor is a nickel-containing hydroxide, and the molar amount of nickel in the nickel-containing hydroxide accounts for ≥ 60 mol% of the total metal; G. The chemical formula of the positive electrode material precursor is Ni a Co b Mn c M d (OH) e X f ; wherein, 0.6 ≤ a < 1, 0 < b + c + d ≤ 0.4, 1.8 ≤ e ≤ 2.5, 0 ≤ f ≤ 0.2; M is selected from at least one of Mg, Nb, Zr, Y, Al, Zn, Ti, Sr, and X is B4O7 2- and / or MoO4 2- .

5. A method for preparing a positive electrode material precursor according to any one of claims 1 to 4, characterized in that: The method comprises: under the protection of inert gas, adding a nickel-containing metal salt solution, a precipitant solution and a complexing agent solution in parallel into a reaction kettle containing a base liquid to carry out a coprecipitation reaction; The pH value in the coprecipitation reaction is controlled to have a pH decreasing period T1, a first pH plateau period T2, a pH increasing period T3 and a second pH plateau period T4 in sequence.

6. The method according to claim 5, characterized in that The method satisfies at least one of the following conditions: (1) The pH value of the base solution is 11.3-11.8; (2) The ammonia concentration of the base liquid is 3 g / L-7 g / L; (3) During the pH value decreasing period T1, the flow rate of the nickel-containing metal salt solution is controlled to be 6.0% / h-10.5% / h of the reactor volume; (4) During the pH value decreasing period T1, the oxygen content of the gas in the reactor is controlled to be less than 2v%; alternatively, the oxygen content of the gas in the reactor is controlled to be less than 1v%; (5) The reaction time of the pH value decrease period T1 is 2.5h-7.5h; (6) During the pH value decreasing period T1, the stirring speed is controlled to be 800 rpm-1100 rpm; (7) When the pH value reaches the first plateau period T2, the flow rate of the nickel-containing metal salt solution is controlled to be 5.0% / h-8.5% / h of the volume of the reactor; (8) When the pH value reaches the first plateau period T2, the oxygen content of the gas in the reactor is controlled to be 2.0 v%-4.0 v%; (9) The pH value of the first pH plateau period T2 is maintained at 11.0-11.4; (10) When the pH value reaches the first plateau stage T2, the ammonia concentration in the reaction system is controlled to be 3 g / L-6 g / L; (11) The reaction time of the first pH plateau phase T2 is 7.5h-14.5h; (12) When the pH value reaches the first plateau phase T2, the stirring speed is controlled to be 800 rpm-1300 rpm; (13) During the pH rising period T3 and the pH second plateau period T4, the flow rate of the nickel-containing metal salt solution is controlled to be 5.5% / h-8.5% / h of the reactor volume; (14) During the pH rising period T3 and the pH second plateau period T4, the oxygen content of the gas in the reactor is controlled to be less than 1v%; (15) The reaction time of the pH rising period T3 is 2h-5h; (16) The pH value of the second pH plateau period T4 is maintained at 11.3-11.6; (17) When the pH value reaches the second plateau stage T4, the ammonia concentration in the reaction system is controlled to be 3.0 g / L-5.5 g / L; (18) The reaction time of the second pH plateau phase T4 is 25h-60h; (19) During the pH rising period T3 and the pH second plateau period T4, the stirring speed is controlled to be 500 rpm-1050 rpm.

7. The method according to claim 5 or 6, characterized in that: The method satisfies at least one of the following conditions: (1) The precipitant solution comprises a sodium hydroxide solution; (2) The mass fraction of the precipitant solution is 20wt%-40wt%; (3) the complexing agent solution includes an aqueous ammonia solution; (4) The mass fraction of the complexing agent solution is 10wt%-30wt%; (5) The nickel-containing metal salt solution also includes cobalt salt and / or manganese salt; (6) The nickel-containing metal salt solution further contains a solution of a doping element M, wherein the doping element M is independently selected from at least one of Al, Ti, Zr, Cr, Mg, Ba, Nb or Sr; (7) The sum of the molar concentrations of the metal ions in the nickel-containing metal salt solution is 1 mol / L to 3 mol / L; (8) A solution containing an anion X is also introduced into the base liquid, wherein the anion X is MoO4 2- and / or WO4 2- ; (9) A solution containing anions X is also introduced into the base liquid in parallel, wherein the mass concentration of the solution containing anions X is 2 g / L-10 g / L; (10) The temperature of the coprecipitation reaction is controlled to be 50°C-70°C.

8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the positive electrode material of the lithium ion battery includes the positive electrode material precursor according to any one of claims 1 to 4; the positive electrode material of the lithium ion battery is a hollow structure.

9. A lithium ion battery, characterized in that: Comprising the lithium-ion battery positive electrode material as claimed in claim 8.

10. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 9.